Responsiveness Of Community Complaint Services In Gresik Regency Police Department - Madini, Sephia; Tukiman, Tukiman (UNIVERSITAS PAKUAN, 2024)
The purpose of this study was to determine the level of responsiveness of complaint services at the Gresik Regency Resort Police. This research method uses a type of quantitative research with a case study approach. The informants in this study were the head of SPKT, complaints service officers, call center officers and people who had made complaints. The data collection techniques used are observation and interviews. The results showed that in general the Responsiveness Level of Community Complaint Services at the Gresik Regency Resort Police as measured using indicators put forward by Zeithaml consisting of Officers / Administrators Perform Services Quickly, and Officers / Administrators Perform Services Appropriately in a very good category. Responding to Every Customer / Applicant Who Wants to Get Service, Officers / Administrators Perform Services Carefully, Officers / Administrators Perform Services with the Right Time, and All Customer Complaints are Responded to by Officers in the category quite well or quite responsive.